2019
DOI: 10.1007/s12471-019-1267-9
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate non-vitamin K antagonist oral anticoagulants prescriptions: be cautious with dose reductions

Abstract: Background Non-vitamin K antagonist oral anticoagulants (NOACs) are prescribed to patients with atrial fibrillation (AF) to reduce the risk of stroke. Prescribing the correct dose warrants careful consideration of the prevailing dose criteria that differ per NOAC. Electronic systems are useful to intercept prescriptions that are incorrect based on simple ‘primary’ criteria, for example dosing frequency and drug-drug interactions with concomitant medication. However, these systems do not take into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
0
30
0
3
Order By: Relevance
“…Furthermore, clinicians are reluctant to prescribe these drugs to frail patients or those at high risk of bleeding due to the lack of routine monitoring of the anticoagulant effect; they strictly follow the guidelines recommendations regarding the dosing regimen and monitor more often NOACs-treated patients. This unwillingness to prescribe NOACs is also reported in real-world studies in recent years [53,54]. Periodic monitoring of patients greatly improves treatment compliance.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, clinicians are reluctant to prescribe these drugs to frail patients or those at high risk of bleeding due to the lack of routine monitoring of the anticoagulant effect; they strictly follow the guidelines recommendations regarding the dosing regimen and monitor more often NOACs-treated patients. This unwillingness to prescribe NOACs is also reported in real-world studies in recent years [53,54]. Periodic monitoring of patients greatly improves treatment compliance.…”
Section: Discussionmentioning
confidence: 77%
“…In a real-world registry in Spain, the rate of underdosing and overdosing of DOAC therapy was 17.5% (93/530) and 14.9% (79/ 530), respectively [16]. Other retrospective studies conducted abroad indicate that 5.4-17.4% patients are prescribed inappropriate reduced doses of DOACs (Additional file 1: Table S2) [17][18][19][20]. In our study, it was found that the rate of underdosing has been decreasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…Although NOACs have been repeatedly shown to be at least as effective and safe as VKAs in both randomized controlled trials and real-world data, a lack of monitoring could have contributed to a hesitation to shift to a more NOAC based approach. This is not unreasonable, as without a regular check of factors such as renal function, weight or age, patients are often (± 10% in two recent Dutch AFstudies), treated with a too high or too low NOAC dose [16,17]. Moreover, early discontinuation of (N)OAC treatment can be as high as 50% at 6 months in certain patient groups [18,19].…”
Section: Guideline Adherence and Reasons Of Not Prescribing Anticoagumentioning
confidence: 99%
“…15 Duke Clinical Research Institute, Durham, USA. 16 Department of Internal Medicine, Cardiovascular Research Institute Maastricht, Maastricht, the Netherlands. 17 Anticoagulation Clinic Maastricht, Maastricht, the Netherlands.…”
Section: Fundingmentioning
confidence: 99%